2018
DOI: 10.14207/ejsd.2018.v7n4p105
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Firms Participating in a Circular Economy

Abstract: Circular Economy (CE) is today a major concept within the sustainability debate (Geissdoerfer, Savageta, Bocken & Hultinkb, 2017). Its theoretical arguments are widely accepted -especially at a cross-country institutional level -but businesses still seem reluctant to acknowledge it as a revenuemaking paradigm. This ongoing study aims to reveal where, along the value chain, firms are more unaware of CE best practice and/or reluctant to invest. After a comprehensive review of sustainable business models, the au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Ormazabal et al (2018) found three factors associated with CE perception by SMEs: material provision, resources reutilisation, and financial advantages. Regarding the SMEs perceptions about CE implementation, Cristoni and Tonelli (2018) analysed the relevance and maturity of CE practices in Italy. The authors found that sourcing, end‐use and design are the most relevant practices along the value chain, while their maturity is more consistent in distribution and production.…”
Section: Resultsmentioning
confidence: 99%
“…Ormazabal et al (2018) found three factors associated with CE perception by SMEs: material provision, resources reutilisation, and financial advantages. Regarding the SMEs perceptions about CE implementation, Cristoni and Tonelli (2018) analysed the relevance and maturity of CE practices in Italy. The authors found that sourcing, end‐use and design are the most relevant practices along the value chain, while their maturity is more consistent in distribution and production.…”
Section: Resultsmentioning
confidence: 99%
“…Only a small fraction of investigated organizations presents a dedicated set of key performance indicators (KPIs) to their approach to CE. Similarly, some studies point towards low consciousness of the CE potential across various industries, and even lower levels of "alleged CE maturity" [16] (p. 107). Among others, [17] touches upon the importance of CE measurement tools by stating that to "( .…”
Section: Introductionmentioning
confidence: 99%
“…This subset of the sample is less sectoral driven and more focused on stakeholder perceptions and challenges and limitations for circular business models and business-model innovation for CE [54,105,110]. From a business organisation perspective, several papers mention firms' low awareness of the CE potential, considering it too costly and risky, especially SMEs [111]. On the user/demand side, user willingness to participate and/or adopt circular business models is also addressed, bridging the gap between supply/demand side innovation and stressing the need to engage stakeholders along the process of transformation [112][113][114][115].…”
Section: Consumption and Use-new Business Modelsmentioning
confidence: 99%